Antibiotic Susceptibility of Bacteria isolated from Estuarine Environment, Turtle Sanctuary and High-Density Industrial Zone in Davao City, Philippines - Aya-ay Adorico M.; San Juan Maria Eva C.; Badong Venchie C.; Baslot Maria Theresa C.; Duarte Rachel C.; Anonuevo Loreniel E.; Fernandez Valerie L. (E3S Web of Conferences)
The study determined the antibiotic susceptibility of bacteria in surface water from estuarine, sanctuary, and industrial zones in Davao City. Researchers examined the spatial distribution of heavy metals and contamination by enteric bacteria using selective media and the Kirby-Bauer Test. The Antibiotic Resistance Index (ARI) revealed that all sites were comparably contaminated with pathogenic bacteria. These findings provide baseline data for government guidelines on waste management and highlight the need for effective water treatment to combat antibiotic-resistant infections.